(3SQ GdUfGYIs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s ((3YHOGdQMef Hf YeGQ Hf NjQj s)
(3ChdgG (B:s
(3QSeJ CWGd Gddg HbGAc hCMSf GJHGY GdYde hCgdg Hc Cf CVY cJGHkG jTJed Ydi LejY CMcGe MQha GdeYLe s
(3BNQgG (B:s
(3aEf CeQJ bdJ hgjG hgh jGQLGd, hgj hgjG hgjf GdhGh gPG BNQ cJGHfG GdeDShe HSQ GdUfGYI s
(3aj GdMQha GdeaQOI eged GdfbW CMjGfkGs
(3HChdgG Cf GdcQGS GdChd efgG HNW GdTjN ceGd GdOjf GHf GdgeGes
(3hJedc YHOGdHGSW Hf eMeO Hf CfhQ Gdecj GdTGaYj NWjH HdO Gddg GdMQGe aj SfI (B966(3g``s
(3Ke Jedc HYOg SfI (B968(3g`` s
(3aj GdeYgO fSNI CNQi HGSe SQ UfG s
(3fSNI KGfjI s
Keywords: (3GdfMhs